Salmonella enterica serovar Paratyphi A isolated from a hard-to-heal diabetic ulcer: a case report - Dilhari, A; Pathirana, S.; Fernando, N. (My University, 2020)
Chronically infected diabetic wounds have a polyrn'crobial aetiology. However. Salmonella Paratyphi A is a very rare cause of wound infection. A 76-year-old female patient with type II diabetes presented with a wound on the left leg of two months' duration. The wound was painful, erythematous and a thick, foul-smelling discharge was present. There was a history of delayed wound healing. Salmonella Paratyphi A and Pseudomonas aeruginosa were isolated from the wound tissue. The patient was treated with cefuroxime and cloxacillin empirically and following the antibiotic susceptibility'testing (ABST) report, ciprofloxacin was given for 10 days. The wound was treated with multiple debridements and topical antiseptic. On follow-up, the patient remained afebrile with subsiding discharge from the ulcer, This is the first reported case of Salmonella Paratyphi A from an infected diabetic ulcer in Sri Lanka and it serves to further define the spectrum of illnesses caused by this uncommon pathogen.
Keywords: diabetes • hard-to-heal wound • infection • Pseudomonas • Salmonella